Lithuanian women in science: management facets - Ina Dagytė (Business: Theory and Practice, 2008)
Though the proportion of women community in Lithuanian science and research and the interest in this phenomenon by representatives of different scientists are growing, yet the many unsolved or inefficiently solved problems, from thepoint of view of management, are signalled by certain characteristics of women scientists` social strata, efficiency of work,indexes of career development and acknowledgement processes. The article seeks to overview the experience of the Lithuanian women scientists within the period of 19902005 and identify the premises for the solution of the main managementproblems in the gender relations. The work uses the following methods of research: analysis, synthesis, observation, expertreview, comparison, structuring. The methods revealed the lack of the transformation management; the missing links inmanagement structures; the absence of legal acts to give assessment of the gender equality. The emerging and commendableself-management aspects and results in women society and within it in the women scientists` social strata are stressed. Theresults are manifested in the 3rd and 4th national congresses of Lithuanian women in 2000 and 2005.